Eigenvalue approach on a problem of magneto-thermoelastic rotating medium with variable thermal conductivity: comparisons of three theories. Issue 6 (2nd November 2021) - Said, Samia M.
Abstract : In the present article, we apply the eigenvalue approach on the two-dimension problem of thermoelasticity in the context of the Green-Lindsay theory (G-L) with two relaxation times, coupled theory (CD) and Lord- Shulman theory (L-S) with one relaxation time. The governing equations of the thermoelastic medium with two temperatures are solved for surface wave solutions. The numerical estimates of the quantities of physical interest is obtained and depicted graphically. Some comparisons of the thermophysical quantities are shown in figures to study the effects of the variable thermal conductivity, two-temperature parameter, rotation, magnetic field, and mechanical force.